Prevalence, clinical associations, and impact of intimate partner violence among HIV‐infected gay and bisexual men: a population‐based study. Issue 5 (21st November 2012) - Siemieniuk, RAC; Miller, P; Woodman, K; Ko, K; Krentz, HB; Gill, MJ
<x xml:space="preserve">Abstract</x> Objectives Intimate partner violence (IPV) is a risk factor for HIV infection. Little is known, however, about the prevalence, clinical associations, and impact of IPV among patients living with HIV. Methods HIV‐infected gay and bisexual men in Southern Alberta, Canada were screened for IPV between May 2009 and December 2011. The associations with IPV of sociodemographic factors, psychological factors, clinical status, and HIV‐related and HIV‐unrelated hospitalizations, data for which were obtained from a regional database, were evaluated using Poisson regression. Results Of 687 gay and bisexual patients, 22.4% had experienced one or several types of IPV. Patients disclosing IPV were more likely to be Aboriginal [adjusted prevalence ratio (APR) = 2.48; 95% confidence interval (CI) 1.18–5.20], to be younger (APR/year = 0.97; 95% CI 0.95–0.99), to be victims of childhood abuse (APR = 4.27; 95% CI 2.84–6.41), to be smokers (APR = 2.53; 95% CI 1.59–4.00), to have had depression prior to HIV diagnosis (APR = 1.87; 95% CI 1.10–3.16), to use ongoing psychiatric resources (APR = 3.53; 95% CI 2.05–6.10), to have recently participated in unprotected sex (APR = 2.29; 95% CI 1.10–4.77), and to have poor or fair vs. very good or excellent health‐related quality of life (APR = 2.91; 95% CI 1.57–5.39). IPV was also associated with a higher rate of clinically relevant interruptions in care (APR = 1.95; 95% CI 1.23–3.08), a higher incidence of AIDS among patients presenting early to care (CD4 count ≥ 200 cells/μL; APR = 2.06; 95% CI 1.15–3.69), and an increased rate of HIV‐related hospitalizations [relative risk (RR) = 1.55; 95% CI 0.99–2.33], especially after HIV diagnosis was established (RR = 2.46; 95% CI 1.51–3.99). Conclusions The prevalence of IPV is high among HIV‐infected gay and bisexual men and is associated with poor social, psychiatric, and medical outcomes. IPV is an under‐recognized social determinant of health in this community that may be amenable to meaningful clinical interventions.